2009
DOI: 10.1897/08-498.1
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine Contaminants in Fishes from Coastal Waters West of Amukta Pass, Aleutian Islands, Alaska, USA

Abstract: Organochlorines were examined in liver and stable isotopes in muscle of fishes from the western Aleutian Islands, Alaska, in relation to islands or locations affected by military occupation. Pacific cod (Gadus macrocephalus), Pacific halibut (Hippoglossus stenolepis), and rock greenling (Hexagrammos lagocephalus) were collected from nearshore waters at contemporary (decommissioned) and historical (World War II) military locations, as well as at reference locations. Total (Sigma) polychlorinated biphenyls (PCBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…Most other studies of the occurrences of DDT isomers/metabolites in fish showed p,p'-DDE to be the predominant form of DDT (Wang et al, 1996;Thomas et al, 2012;Miles et al, 2009;Yang et al, 2006). In our study, it was the second most concentrated isomer/metabolite, slightly less concentrated than p,p'-DDD.…”
Section: Decrease In Concentrations Of Total Ddt and Ddt Isomers/ Metsupporting
confidence: 55%
See 2 more Smart Citations
“…Most other studies of the occurrences of DDT isomers/metabolites in fish showed p,p'-DDE to be the predominant form of DDT (Wang et al, 1996;Thomas et al, 2012;Miles et al, 2009;Yang et al, 2006). In our study, it was the second most concentrated isomer/metabolite, slightly less concentrated than p,p'-DDD.…”
Section: Decrease In Concentrations Of Total Ddt and Ddt Isomers/ Metsupporting
confidence: 55%
“…EF data, along with concentration data for all six congeners and DDA, should help indicate transport, transformation and exposure pathways of these pollutants. p,p'-DDT and its isomers/metabolites are "legacy" pollutants that have polluted the environment for seven decades and can still be found in a variety of environmental and human compartments and receptors Miles et al, 2009;Patterson et al, 2009;Thomas, et al, 2012;Vizcaino et al, 2010). The main congeners of DDT found in the environment and related receptors are p,p'-DDT ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aldrin is readily converted to dieldrin (once it enters either the environment or the body), which is considered one of the most persistent of all pesticides (Miles et al 2009;Hogarh et al 2014). These pesticides were used extensively in agriculture until their use was restricted.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas concern regarding the long-range transport of PCBs to the Arctic has been the focus of a number of studies (Macdonald et al, 2000; Wania, 2003), the influence of local point sources, such as the large number of sites associated with the Distant Early Warning (DEW) line in Canada, and formerly used defense sites (FUDS) in Alaska, is of continuing concern to residents who live in close proximity to those sites (Ap O’Hehir et al, 2005), many of whom rely on wildlife for subsistence. While a great deal of effort has been directed towards remediation of several DEW and FUDS contaminated sites (Poland et al, 2001; Stow et al, 2005), with clean-up efforts resulting in lower exposures of PCBs (Brown et al, 2009), sites that remain contaminated continue to influence PCB levels in wildlife (Anthony et al, 2007; Ricca et al, 2008; Miles et al, 2009). …”
Section: Introductionmentioning
confidence: 99%